(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Furt D. V. Multicultural component in philosophical and pedagogical discourses. The article describes the ideas formation process of polycultural education; throws the light on the philosophers’ and educators’ views concerning the principles of polyculture and relationships between different cultures.